2017
DOI: 10.1016/j.jgeb.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Cr(VI) biosorption onto Aspergillus niger using 3-level Box-Behnken design: Equilibrium, kinetic, thermodynamic and regeneration studies

Abstract: Heavy metal biosorption is an efficient technology for the decontamination of metal from industrial waste water. The present study focused on exploration of Aspergillus niger towards removal of Cr(VI) from aqueous solution. The influence of different experimental parameters—initial pH, adsorbent dose, initial concentration, contact time, shaking speed, temperature, and their combined effect during Cr(VI) adsorption—was investigated by means of response surface methodology based on four factorial Box–Behnken ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 31 publications
2
50
0
2
Order By: Relevance
“…This increase in porosity certainly leads to an increase in the adsorption capacity of the adsorbents. Also, the adsorbent has some heterogeneity which is supposed to be the active site for metal binding . Figure c,d shows the adsorbent surface status after adsorption of the Cr (VI) and Cd.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This increase in porosity certainly leads to an increase in the adsorption capacity of the adsorbents. Also, the adsorbent has some heterogeneity which is supposed to be the active site for metal binding . Figure c,d shows the adsorbent surface status after adsorption of the Cr (VI) and Cd.…”
Section: Resultsmentioning
confidence: 99%
“…As seen, the surface and holes of the biomass are well occupied by two metals, so the biomass has had an acceptable adsorption efficiency. Also, SEM pictures also revealed that the surface of fungal biomass ( A. terreus ) is flattened after Cr (VI) and Cd adsorption . As seen in Figure , determination of the surface‐active functional groups on the Aspergillus terreus fungus biomass was performed by FTIR analysis using FTIR spectrophotometer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromium is known as one of the most hazardous heavy metals and is a serious threat . It is used in different industries such as: electroplating, leather tanning, steel industry, textile dyeing, paint and pigment formulation, refractory materials, mining, wood preservation, cement, alloys, photographic materials, and is discharged in the environment through their wastes . Trivalent and hexavalent chromium are the most common forms in the environment .…”
Section: Introductionmentioning
confidence: 99%
“…Considering the points mentioned above, recovery or removal of heavy metals from aqueous media is one of the top priorities. So, researches are still performed on procedures that are both economical and eco‐friendly . Recently, different techniques have been improved for the treatment of heavy metal containing wastewaters, to decrease the wastewaters' quantity and increase the treated wastewaters' quality .…”
Section: Introductionmentioning
confidence: 99%